2018
DOI: 10.1159/000488952
|View full text |Cite
|
Sign up to set email alerts
|

The cGAS/STING Pathway Is Important for Dendritic Cell Activation but Is Not Essential to Induce Protective Immunity against <b><i>Mycobacterium tuberculosis</i></b> Infection

Abstract: Mycobacterium tuberculosis (Mtb) infection remains a major public health concern. The STING (stimulator of interferon genes) pathway contributes to the cytosolic surveillance of host cells. Most studies on the role of STING activation in Mtb infection have focused on macrophages. Moreover, a detailed investigation of the role of STING during Mtb infection in vivo is required. Here, we deciphered the involvement of STING in the activation of dendritic cells (DCs) and the host response to Mtb infection in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 41 publications
0
31
0
1
Order By: Relevance
“…Previous study reported that M. bovis induced the induction of proinflammatory cytokines via activation of NF-κB signaling pathway in macrophages (Wang et al, 2016). However, recent study reported that NaB inhibited LPS-induced NF-κB signaling (Marinho et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Previous study reported that M. bovis induced the induction of proinflammatory cytokines via activation of NF-κB signaling pathway in macrophages (Wang et al, 2016). However, recent study reported that NaB inhibited LPS-induced NF-κB signaling (Marinho et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…The duality of the STING adaptor molecule, sensing nucleic acids from both the host and the pathogen, is central to explaining the exacerbated response to silica pre-exposure plus M. tuberculosis infection. STING is activated after M. tuberculosis infection in vivo (Collins et al, 2015;Marinho et al, 2018); however, silica pre-exposure induces STING expression and leads to the exacerbation of STING aggregation in the perinuclear region of host cells after M. tuberculosis infection. Administration of M.tb DNA in vivo leads to STING activation and recapitulates STING aggregation after silica pre-conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis residing in the macrophage release DNA, which is detected by the cytosolic surveillance system through cyclic guanosine monophosphate (cGMP)-AMP synthase (cGAS), triggering activation of the stimulator of IFN genes (STING) adaptor molecule and inducing IFNI responses (Collins et al, 2015;Manzanillo et al, 2012;Wassermann et al, 2015;Watson et al, 2015). While the STING pathway contributes to the host response to infection, including bacterial infections (Marinho et al, 2017), it does not seem essential to control in vivo M. tuberculosis infection (Collins et al, 2015;Marinho et al, 2018). (legend continued on next page)…”
Section: Introductionmentioning
confidence: 99%
“…The cGAS/STING pathway is essential for DC activation 35 both Sting-sufficient and Sting-deficient mice ( Fig. 5A and 5C).…”
Section: Sting Activation Promotes the Maturation Of Dendritic Cells mentioning
confidence: 97%